Leprosy- Atypical Presentation with Reaction - Khan, Mohammad Mofizul Islam (Journal of Armed Forces Medical College, Bangladesh, 2024)
Leprosy is a chronic granulomatous disease affecting mainly the skin and nerves caused by the obligate intracellular pathogen Mycobacterium leprae. Patient not always present with typical skin lesion with loss of sensation or muscle weakness rather may present with atypical skin lesion with swelling of the affected area like cellulites or lymphangitis as reactional state. A 25- years-old male patient presented with linear erythematous verrucous plaque along with multiple nodules and pain and swelling of left upper extremity. Local examination revealed sensory loss on inner aspect of left hand and finger and ulner nerve found enlarged, thickened and tender. Slit skin smear showed numerous lepra bacilli. Skin biopsy for histopathology showed collection of foamy histocytes forming granuloma within the upper dermis and wade fite staining, moderate number of lepra bacilli was seen. Patient was diagnosed as a case of borderline leprosy with type 1 lepra reaction. Patient was getting treatment with MDT (multi drug therapy) and systemic steroid and responded very well. His skin lesions are almost subsided and weakness of hand was recovering gradually. JAFMC Bangladesh. Vol 19, No 1 (June) 2023: 76-79